Real-time implementation of nonlinear optimal-based vibration control for a wind turbine model. Issue 3 (December 2019) - Martynowicz, Paweł
In the present paper, a real-time implementation of a previously introduced nonlinear optimal-based vibration control method is presented. A vibrating structure, namely a wind turbine tower-nacelle laboratory model equipped with a tuned vibration absorber, is analysed. For control purposes, a magnetorheological damper is used in a tuned vibration absorber system. Force constraints of a magnetorheological damper are an intrinsic part of the implemented nonlinear technique. The aim of the current research is to experimentally investigate the influence of nonlinear optimal-based vibration control law quality index elements' weights on the vibration attenuation effectiveness along with the magnetorheological damper stroke amplitude, maximum control current or force. As a reference, simple, optimal-based, modified ground-hook law with the sole control objective of primary structure deflection minimisation is used in addition to the passive systems with constant magnetorheological damper current values, proving the benefits of the proposed solution.